Aerobic endurance performance does not determine the professional career of elite youth soccer players - Castillo, D.; Los Arcos, A.; Martinez-Santos, R. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Physical characteristics have been widely analyzed in order to understand why some soccer players are more successful than others. Therefore, the aims of this study were: 1) to describe the evolution of aerobic endurance performance across 18 years in a Spanish elite soccer academy; 2) to know if the playing position could affect physical testing performance; and 3) to look into the alleged impact of this factor on the professional career of soccer players.